Prostate cancer incidence and mortality in Portugal: trends, projections and regional differences. Issue 5 (September 2017) - Pina, Francisco; Castro, Clara; Ferro, Ana; Bento, Maria J.; Lunet, Nuno
Abstract : There is a large geographical variability in prostate cancer incidence and mortality trends, mostly because of heterogeneity in control efforts across regions. We aimed to describe the time trends in prostate cancer incidence and mortality in Portugal, overall and by region, and to estimate the number of incident cases and deaths in 2020. The number of cases and incidence rates in 1998–2009 were collected from the Regional Cancer Registries. The number of deaths and mortality rates were obtained from the WHO mortality database (1988–2003 and 2007–2013) and Statistics Portugal (2004–2006; 1991–2013 by region). JoinPoint analyses were used to identify significant changes in trends in age-standardized incidence and mortality rates. Incidence and mortality predictions for 2020 were performed using Poisson regression models and population projections provided by Statistics Portugal. In Portugal, prostate cancer incidence has been increasing since 1998 (1.8%/year), with the exception of the North Region, with a decrease since 2006 (−3.2%/year). An overall mortality decline has been observed since 1997 (−2.2%/year), although there were two patterns of mortality variation at the regional level: one with an inflection point or significant variation in the rates and the other without significant variation. If these trends are maintained, ∼8600 incident cases and 1700 deaths may be expected to occur in Portugal in 2020. Despite the overall increasing incidence and decreasing mortality, there is a large heterogeneity across regions. Future studies should address regional differences in the trends of prostate specific antigen screening and in the effective management of prostate cancer.